(untitled) (Journal of Namibian Studies : History Politics Culture, 2021)
This paper explores two broad aspects of the history of the spread of Muslims and their faith in the eastern frontier of South Asia. First, it traces the history of the Muslim conquest and spread of Islam in the Bengal frontier, particularly in Sylhet proper and its southern most part, known in medieval times as Taraf (now a part of Habiganj District, in Bangladesh), and further entry and settlement of Muslims from these regions to Manipur. Second, the paper examines the mention of Mughals in the royal chronicles of the rulers of Manipur and puyas, or old historical manuscripts, and the instances of the settlement of Mughals in Manipur during the course of Mughals’ political expansion in the eastern frontier of South Asia in the 16th and 17th century.